North American economic and financial integration - Rugman, Alan M. (Emerald, 2004)
This book contains selected papers first presented at the Canada-United States Business Conference held at the Kelley School of Business, Indiana University, on April 11-12, 2003. The set of 18 chapters in this book are grouped into three major sections. Part I deals with regional economic integration in North America, including papers on the strategies of multinational enterprises and exporting firms. In Part II, five chapters deal with financial integration in North America and the issues of a common currency.Finally, specific industry sectors and issues of public policy across the Canada-U.S. border are examined in Part III. They include: agriculture; softwood lumber; transportation; and electricity. The key issues of current interest and concern examined include: cross border trade and security - of particular importance in the post-9/11 environment; NAFTA at age ten; and the impact of the Free Trade of the Americas (FTAA) on NAFTA; and, the FTAA and civil society. The key policy areas discussed included regulation, labor mobility, productivity, and specific sectoral issues (energy, transportation, etc.). In addition to this examination of key research issues, authors also explore managerial and public policy implications of their findings.
Keywords: Business & Economics -- Management.; Social Science -- General.; International economics.; Production & quality control management.; North America -- Economic integration.; elektronické knihy; electronic books